Go-Byar Based on Virtual Reality for the Learning Media of Gamelan - Kadek Dwipayana; I Made Agus Wirawan; I Gede Partha Sindu (Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
Gong Kebyar is one of the group of Balinese music that has five pelog tones which the playing technique using kebyar system. Gong Kebyar serves the instrumental performances, accompanying various types of dances, and accompanying Himdu's religious ceremonial activities in Bali. But not many young people can play the gong kebyar due to lack of adequate facilities. One effort that can be done is to utilize virtual reality technology as an instructional media for playing Gong Kebyar. The purpose of the study was to design and implement the design of Gamelan Gong Kebyar based on Virtual Reality.The development of the Gamelan Gong Kebyar Game based on Virtual Reality was implemented using the ADDIE model. The main feature of this game was playing the gamelan Gong Kebyar instrument, besides that there is a feature playing the instrument accompanied by the song so that the player could feel the situation of playing it in form of sekaa. The design is using a functional model which is UML (Unified Modeling Language) and implemented using programming language C# which edited by MonoDevelop-Unity. The results of this study is a Gong Kebyar application based on virtual reality which is operated with a computer and HTC VIVE VR device. All features in this application function properly. With this application, the community can learn to play Gong Kebyar with the results of the user response test obtaining a value of 91%, which means it is included in the excellent category.